Reaction to problem X of some Brazilian varieties of beans (Phaseolus vulgaris L.) - Menten, J.O.M.; Castaño, M. (1980)
Thirty-nine Brazilian bean var. were evaluated for their resistance to problem X originated in the soil and detected in Colombia. Eleven materials previously evaluated were used as controls. The plants, grown in pots with soil collected at the places where the problem is common, were evaluated 20 and 30 days after seedling emergence using a scale of 1 (no symptoms) to 5 (serious malformation of leaves and plants). The reaction to problem X among the Brazilian var. varied widely. Var. Enxofre was the most resistant (no symptoms). The most common cv. in Brazil showed the following reactions, evaluated at 20 and 30 days, resp.: Goiano Precoce, 2 and 3; Rosinha G-2, 3 and 3; Roxo, 3 and 3; Rico 23, 4 and 3; Bico de Ouro, 3 and 4; Carioca, 4 and 5; Aete, 5 and 5. (CIAT)